2019
DOI: 10.3390/jcm8040462
|View full text |Cite
|
Sign up to set email alerts
|

Effective Diagnosis and Treatment through Content-Based Medical Image Retrieval (CBMIR) by Using Artificial Intelligence

Abstract: Medical-image-based diagnosis is a tedious task‚ and small lesions in various medical images can be overlooked by medical experts due to the limited attention span of the human visual system, which can adversely affect medical treatment. However, this problem can be resolved by exploring similar cases in the previous medical database through an efficient content-based medical image retrieval (CBMIR) system. In the past few years, heterogeneous medical imaging databases have been growing rapidly with the advent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 54 publications
(115 reference statements)
0
56
0
Order By: Relevance
“…In the case of imbalance in the training data of the two classes such as the medical image processing system that is normally faced with the problem of data collection due to special characteristics of medical images, the binary cross-entropy function can produce bias in the trained classifier. To solve this problem, our proposed method uses a modified version of the binary cross-entropy, called the Weighted Binary Cross-Entropy (wBCE), as shown in Equation (6). As shown in this equation, we assigned different weight values to the losses caused by samples in each class in the binary cross-entropy function.…”
Section: Weighted Binary Cross-entropy Loss Function For Compensatingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of imbalance in the training data of the two classes such as the medical image processing system that is normally faced with the problem of data collection due to special characteristics of medical images, the binary cross-entropy function can produce bias in the trained classifier. To solve this problem, our proposed method uses a modified version of the binary cross-entropy, called the Weighted Binary Cross-Entropy (wBCE), as shown in Equation (6). As shown in this equation, we assigned different weight values to the losses caused by samples in each class in the binary cross-entropy function.…”
Section: Weighted Binary Cross-entropy Loss Function For Compensatingmentioning
confidence: 99%
“…As a result, the diagnostic performance varies and is limited. With the development of digital technology, image-based diagnosis techniques have been widely used to help doctors investigate problems with organs that are underneath the skin and/or deep inside the human body [1][2][3][4][5][6][7][8][9][10][11]. For example, doctors have used X-ray imaging to capture lung and/or bone images that can help to indicate whether a disease/injury exists in these organs [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, large curated image databases, such as The Cancer Imaging Archive (TCIA), [ 26 ] provide quality control and regulatory clearance of cancer‐related medical images under standardized Digital Imaging and Communications in Medicine (DICOM) standards [ 27 ] for a wide range of data including chests X‐rays, computed tomography, ultrasound and magnetic resonance imaging. [ 28–32 ] Thus, for deep learning applications, a facilitated path from technical feasibility to medical outcomes adjudication has underpinned much of the current success. A recent clinical trial studying the use of deep learning to identify images of diabetic retinopathy has resulted in the first FDA approved use of an autonomous AI diagnostic.…”
Section: Trends In Artificial Intelligence and Deep Learningmentioning
confidence: 99%
“…Recent years have shown that some advances in machine learning algorithms called 'Deep Learning (DL)' [10] is introduced for solving the above problems. The conventional machine learning methods have used "shallow" architectures, while deep learning act like human brain where it is organized as deep architecture and processes data in multiple stages of representation and transformation [11] [12]. There are many open-source libraries such as TensorFlow (https://www.tensorflow.org) and PyTorch (https://pytorch.org/ ) that allow the creation of deep neural nets in Python .…”
Section: Introductionmentioning
confidence: 99%